The perceptions of nurses, patients and family members regarding nurses' empathetic behaviours towards patients suffering from cancer: a descriptive qualitative study - Ashouri, Elaheh (J Res Nurs, 2018)
BACKGROUND: Although evidence suggests that empathic behaviour is an essential component in nursing care that affects the psychological distress experienced by cancer patients, it remains a neglected issue in nursing in Iran. METHODS: This study was conducted on 33 participants selected through purposive sampling. Data were collected using in-depth interviews and were then analysed using qualitative content analysis with an inductive approach. FINDINGS: Three categories of data thus emerged, comprising: (a) empathetic attention; (b) empathetic presence; and (c) the facilitators of empathetic behaviour. CONCLUSIONS: The findings can help oncology nurses provide more empathetic care to patients and their family members.